Research methods - White, Theresa L.; McBurney, Donald H. (Wadsworth Cengage Learning, 2013)
Research Methods' is a succinct, straightforward guide designed to complement any research methods in psychology course. Throughout, the authors offer many student-friendly activities that encourage learning by fostering students' participation in the research process.